THE USE OF THE AGROPHOTOVOLTAIC SYSTEMS – A METHOD FOR THE SUPPORTING SUSTAINABILITY - ANGHEL MĂDĂLINA-GABRIELA; STRIJEK DENIS-ARTHUR (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The crisis in the energy sector that the European Union has faced in recent years, as a result of the armed conflict between Ukraine and Russia, has forced national and European authorities to turn to alternative sources of energy. In this context, the objective of the authors in this article is to identify the extent to which the introduction of agrophotovoltaic systems in Romania contributes to the diversification of the energy mix, simultaneously realizing a reterritorialization of the land, by using the space around the photovoltaic panels for agricultural crops or other complementary destinations, a concept known as agrophotovoltaics. The agrophotovoltaic model involves the integration of photovoltaic panels with agricultural activities on the same land, optimizing both uses. By using the agro-photovoltaic model, a link can be made between renewable energy production and agriculture, participating in a greener and more resilient economy. The research methodology consisted in the use of time series, based on the data published by the Romanian National Institute of Statistics and Eurostat. Both structurally and dynamically, indicators such as share of energy from renewable sources in the European Union or solar energy produced in photovoltaic installations were studied. For a better understanding of the data, they were represented in tabular and graphical form. Following the study, it can be found that the system that combines the production of green energy with agricultural activities contributes to the efficient use of land and the improvement of sustainability. At the same time, the upward evolution of green energy sources, especially solar energy and wind energy, is evident.